Features pathogenetic therapy of vaginal infections during pregnancy - A. A. Balushkina (Медицинский совет, 2019)
Vaginal infections occupy an important place in the structure of obstetric-gynecological morbidity. Bacterial vaginosis, trichomoniasis and vulvovaginal candidiasis are the most common infectious causes of vaginitis. Foreign and domestic studies indicate a high frequency of adverse obstetric and neonatal outcomes with this pathology: premature termination of pregnancy, placental insufficiency, fetal growth retardation, chorioamnionitis, postpartum suppurative inflammatory diseases and other complications. Patients with ischemic-cervical insufficiency should be assigned to the group at high risk of developing the above complications. The mixed vaginal infections detected in them require the rehabilitation of the birth canal and the elimination of possible pathogens in a short time. In this regard, timely diagnosis and rational treatment of vaginal infection will reduce the frequency of complications of pregnancy, childbirth, the postpartum period, and neonatal morbidity.